Single-Dose Intralesional Bacillus Calmette-Guérin (BCG) Immunotherapy Induces Complete and Sustained Remission of Recalcitrant Anogenital Condylomata: A Mechanistic Case Series - Azhar Arrosyid; Prasetyadi Mawardi; Endra Yustin Ellistasari; Ammarilis Murastami (HM Publisher, 2026)
Background: Anogenital condylomata acuminata caused by Human Papillomavirus (HPV) presents a significant therapeutic challenge due to high recurrence rates after conventional cytodestructive therapies. Intralesional immunotherapy aims to induce a host-mediated immune response, offering a promising alternative. This report investigates the efficacy, safety, and immunological rationale of a novel, single-dose Bacillus Calmette-Guérin (BCG) protocol in an immunologically primed population. Methods: In this prospective case series, three immunocompetent patients with extensive, therapy-refractory anogenital condylomata were enrolled. Following a standardized protocol, each patient received a single, calculated intralesional injection of BCG vaccine into the largest index lesion. The primary outcome was complete clinical and dermoscopic clearance. Patients were evaluated at regular intervals for efficacy and safety over a 12-month follow-up period. Result: All three patients achieved complete clinical and dermoscopic clearance of both the injected and distant, untreated lesions within a rapid timeframe of 6 to 10 weeks. The treatment was well-tolerated, with adverse events limited to anticipated and transient local inflammatory reactions. No recurrences were documented in any patient during the 12-month follow-up period. Conclusion: Single-dose intralesional BCG immunotherapy appears to be a highly effective, durable, and safe therapeutic strategy for recalcitrant anogenital condylomata. The observed pan-lesional clearance strongly suggests the induction of a systemic, cell-mediated anti-HPV immune response. These compelling preliminary findings provide a strong rationale for validation through larger, randomized controlled trials.